Associations Between Uncertainty Stress, Life Stress and Internet Addiction Among Medical Students - Yang, Qian; Wu, Zhihua; Yang, Xiaozhao; Jiang, Shuhan; Wu, Dan; Oliffe, John L. (Frontiers in Public Health, 2022)
Objectives: Internet Addiction (IA) is a growing issue predominate in adolescents and young adults. Although the effects of diverse stressors on IA have been highlighted, there is little consensus about the specific underpinnings of IA. The current study aims to investigate associations between uncertainty stress, life stress and IA among Chinese university medical students. Methods: A cross-sectional survey employing multi-stage sampling was used. Data were collected from 6061 students from 27 university medical programs across China. Associations between uncertainty stress, life stress, and IA were examined by means of multiple linear regression and indirect effect models. Results: After controlling for respondents’ demographics (i.e., age, sex, and monthly expenses), the findings indicated that the overall IA prevalence was 11.8% (95% CI 11.7 - 12.43 %). Uncertainty stress [adjusted OR 2.56 (95% CI 2.11 – 3.10), P<0.001] and life stress [adjusted OR 1.70 (95% CI 1.31 – 2.21), P<0.001] were positively associated with IA. Population Attributable Risk (PAR) of uncertainty stress associated with IA was 25%, and that of life stress was 5%. Conclusions: The contribution of uncertainty stress to IA is significantly higher than that of life stress. High uncertainty stress, being male and higher socio-economic status were associated with excessive Internet use and IA.